2018
DOI: 10.1021/acssuschemeng.8b00524
|View full text |Cite
|
Sign up to set email alerts
|

Improved Hydrogen Evolution Reaction Performance using MoS2–WS2 Heterostructures by Physicochemical Process

Abstract: This report describes the synthesis of a layered molybdenum disulfide (MoS2)–tungsten disulfide (WS2) heterostructure onto fluorine doped tin oxide covered glass substrates using a combination of chemical bath deposition and RF sputtering techniques. FESEM images revealed that the MoS2–WS2 heterostructure surface consisted of a cauliflower structured array of grains with spherical structures. The vertically aligned atomic layers were explored by transmission electron microscopy images for MoS2–WS2 heterostruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
102
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 51 publications
1
102
0
Order By: Relevance
“…For example, Vikraman et al demonstrated the improved HER performance using MoS 2 –WS 2 heterostructures owing to the elevation of electron–hole separation at the layer interfaces and sharing of active edge sites through the interface. [ 157 ] Kwon et al have improved the HER catalytic performance of MoS 2 through the formation of n‐TMD/p‐TMD heterojunctions to use the high electric fields in the p–n junction. [ 158 ] Although the fabrication of these materials is not simple enough, the concept of the adhesion energy and charge injection can be well employed in building the hybrid structure that we have discussed above.…”
Section: Progress On Strategies To Improve the Her Catalytic Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Vikraman et al demonstrated the improved HER performance using MoS 2 –WS 2 heterostructures owing to the elevation of electron–hole separation at the layer interfaces and sharing of active edge sites through the interface. [ 157 ] Kwon et al have improved the HER catalytic performance of MoS 2 through the formation of n‐TMD/p‐TMD heterojunctions to use the high electric fields in the p–n junction. [ 158 ] Although the fabrication of these materials is not simple enough, the concept of the adhesion energy and charge injection can be well employed in building the hybrid structure that we have discussed above.…”
Section: Progress On Strategies To Improve the Her Catalytic Activitymentioning
confidence: 99%
“…Another powerful aspect of TMD catalysis that can be used in complement to the techniques we have discussed is the fabrication of chemically functionalized TMDs, these functionalities can include noble metals as we have discussed above, and also the metal organic frameworks, layered perovskites, hybrid structures or organic group functionalization. [ 156–158,192–196 ] This is an emerging a powerful field as it opens a whole new set of possibilities to active the catalytically active sites of TMDs and add catalytic activity, via the functional moiety, to inactive sites on the pristine TMD for both acidic and alkaline HER. Since heterostructuring is hugely flexible owing to van der Waals stacking, unique electronic band structures (e.g., tune the Δ G H* and enable improved charge injection between interfaces) can be fabricated and tested in an extremely simple and controllable manner.…”
Section: Conclusion and Prospectmentioning
confidence: 99%
See 1 more Smart Citation
“…To enhance the HER activity of MoS 2 , theoretical and experimental studies have proposed anchoring of Co atoms and cobaloxime on the inert basal plane of MoS 2 , engineering in the defects sites and using metallic 1T‐MoS 2 . Remarkable advances in heterostructure designs such as MoS 2 /graphene superlattices, nanosized MoS 2 /graphene hybrids, nonmetal plasmonic MoS 2 /TiO 2 heterostructure and MoS 2 ‐WS 2 heterostructures by physiochemical process have led to enhanced HER activity . Some studies have also revealed enhanced HER activity by virtue of active sites …”
Section: Introductionmentioning
confidence: 99%
“…[13] Remarkable advances in heterostructure designs such as MoS 2 /graphene superlattices, [14] nanosized MoS 2 /graphene hybrids, [15] nonmetal plasmonic MoS 2 /TiO 2 heterostructure [16] and MoS 2 -WS 2 heterostructures by physiochemical process have led to enhanced HER activity. [17] Some studies have also revealed enhanced HER activity by virtue of active sites. [18a-d] Covalently cross-linked graphene sheets have been investigated primarily for the surface area and gas adsorption properties.…”
Section: Introductionmentioning
confidence: 99%